PENGARUH KOORDINASI DALAM PELAKSANAAN DISIPLIN KERJA PEGAWAI DI SEKRETARIAT DINAS PANGAN, TANAMAN PANGAN DAN HORTIKULTURA PROVINSI KALIMANTAN TIMUR - Indra Kusuma Wardana (ADMINISTRASI PUBLIK, 2019)
This study aims to Knowing me influence coordination In Implementation Discipline Work Employees at the Secretariat Service Food, Plants Food and Horticulture East Kalimantan Province inimplementation discipline work employee.The method used is asossiatif with quantitative analysis and The population of this study were 3 Civil Servants 4 people At the Secretariat Service Food , Plants Food and Horticulture East Kalimantan Province , while the supporting techniques are observation, interview and documentation.This study uses data analysis techniques used correlation coefficient analysis with product moment correlation formula then it can be seen that leadership coordination factors have a significant and positive effect on employee performance at the Secretariat Service Food , Plants Food and Horticulture East Kalimantan Province proven by So interpretation is coordination will followed with implementation discipline work employee , Based on analyzes that , then hypothesis that is the researcher submit is that H 0 in reject and H 1 acceptedmeaning there is influence between coordination in implementation discipline Gov employee At the Secretariat Service Food , Plants Food and Horticulture East Kalimantan Province.